Pengaruh Kualitas Produk, Pesan Iklan, Dan Word Of Mouth Terhadap Keputusan Pembelian Produk Kosmetik Marina - Ependi, Winda Aprilia; Realize, Realize (STIE Wiyatamandala, 2023)
The purpose of this research is to examine how product quality, advertising messages, and word of mouth partially or simultaneously affect the decision to purchase Marina cosmetics. Can use the type of research related to associative with a quantitative research approach. Due to the fact that the population used by buyers or users of Marina cosmetics is not known with certainty, and the sample size determination technique used was the Jacob-Cohen formula, 204 respondents were obtained which were used to collect respondent data. The sampling technique uses purposive sampling as a targeted sampling method. Validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, analysis of the coefficient of determination (R2), t test and f test can be used in the data analysis process during the research. The results of the study can show that product quality, advertising messages, and word of mouth partially or simultaneously or together can influence the decision to purchase Marina cosmetics